Cervical lymphadenopathies: a diagnostic crisis - Joy, Priya; Gayathri, G.; Gangadharan, V. (International Journal of Advances in Medicine, 2017)
Cervical lymphadenopathy refers to lymphadenopathy of the cervical lymph nodes. The causes are varied, and may be inflammatory, degenerative, infective or neoplastic. The first case presented here is of a 29-year old male presented with h/o recurrent progressive right sided painless swelling in the infraparotid region with cervical lymphadenopathy for past one year. Swelling was 6×6cm, nontender, firm mass. Cervical lymph nodes were palpable. He had raised eosinophil counts and elevated serum IgE levels. Biopsy showed abundant eosinophilic infiltration with microabscess suggestive of Kimura’s disease. Second case reported here is of a 17-year old female patient presented with fever for 3 weeks with cervical lymphadenopathy. The lymph node was 3×2cm, tender and firm. Routine blood investigations showed anemia. Biopsy showed lymph nodes composed of sheets of macrophages with crescent shaped nuclei with areas of necrosis and karyhorrhexis suggestive of Kikuchi’s disease. Kimura’s disease is a relatively uncommon chronic inflammatory benign condition mostly affecting the lymph nodes, subcutaneous tissue and salivary glands of head and neck region. It is seen in males in their second decade of lives. Peripheral eosinophilia, regional lymphadenopathy and elevated serum IgE levels are characteristics of Kimura’s disease. Kikuchi-Fujimoto disease is a benign, idiopathic and self-limited disease. Affects young females between 20-35 years of age. Usually there will be localized painful lymphadenopathy, fever and leukopenia. Kikuchi disease runs a benign course and resolves in several weeks to months. The two cases are presented to make clinicians aware of Kimura’s disease and Kikuchi’s disease as a differential diagnosis of cervical lymphadenopathy and to avoid the diagnostic dilemma both clinically and histopathologically.